Playing activity of footballers of 19-20-years-old age in the professional commands of 2-d championship of Ukraine of a football - Balan В.A; Sviridenko A.V (Kharkov National Pedagogical University, 2011)
Data the normatively-legal documents of Federation of football of Ukraine and professional commands (request folias and protocols of matches of 2d championship of Ukraine are from football) served as for research. In research it was attached the construction of the statistical grouping what allowed to analyse in a dynamics playing activity of footballers of 19-20-years-old age on the stage of preparation to the high achievements. Influence of the contention loading is appraised on the organism of sportsmen of this age. Participating of athletes of 19-20-years-old age is set in compositions of professional commands of 2d championship of Ukraine of football.